2014
DOI: 10.1126/science.1239176
|View full text |Cite
|
Sign up to set email alerts
|

Solar Synthesis: Prospects in Visible Light Photocatalysis

Abstract: Chemists have long aspired to synthesize molecules the way that plants do — using sunlight to facilitate the construction of complex molecular architectures. Nevertheless, the use of visible light in photochemical synthesis is fundamentally challenging because organic molecules tend not to interact with the wavelengths of visible light that are most strongly emitted in the solar spectrum. Recent research has begun to leverage the ability of visible light absorbing transition metal complexes to catalyze a broad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
1,013
0
12

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 2,171 publications
(1,067 citation statements)
references
References 79 publications
3
1,013
0
12
Order By: Relevance
“…Inexhaustible solar energy is the most important sustainable resource, whose annual energy output for Earth is capable for satisfying mankind's yearly energy consumption with 5% UV, 43% visible, and 52% IR [9,10]. For today, many applications of solar energy have been proposed, such as photoelectrochemical reaction and various solar cells [5,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27], which are all indirect utilization depending on meticulous devices.…”
Section: Introductionmentioning
confidence: 99%
“…Inexhaustible solar energy is the most important sustainable resource, whose annual energy output for Earth is capable for satisfying mankind's yearly energy consumption with 5% UV, 43% visible, and 52% IR [9,10]. For today, many applications of solar energy have been proposed, such as photoelectrochemical reaction and various solar cells [5,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27], which are all indirect utilization depending on meticulous devices.…”
Section: Introductionmentioning
confidence: 99%
“…3 While the design of heterogeneous photocatalysts has focused largely on semiconducting light absorbers, 4,5 it has recently been demonstrated that metallic nanostructures offer unique characteristics for facilitating photocatalytic reactions. [6][7][8][9] Strong light absorption through the excitation of localized surface plasmons on plasmonic metal nanostructures 10 comprised of Au, [11][12][13] Ag, [14][15][16] Cu, 17 or Al, 18 has been shown to drive photocatalytic processes through the excitation and transient transfer of energetic, or hot, carriers to adsorbates.…”
Section: Main Textmentioning
confidence: 99%
“…From the results of our work, it is clearly demonstrated that organo-photoredox catalyst-such as fac-Ir(ppy) 3 -can facilitate the energy transfer from visible light to the cinnamates system for the activation of the double bond. A plausible pathway was thus proposed, based on the literature precedents [18,30] and experimental data (Scheme 3). Absorbing a photon, the photocatalyst PC(S 0 ) in its singlet ground state is excited to the first singlet excited state *PC(S 1 ), which relaxes to the lowest energy triplet excited state *PC(T 1 ) via successive fast intersystem crossing (ISC) (spin-orbital coupling) and internal conversion (vibrational relaxation).…”
Section: Resultsmentioning
confidence: 99%